2020
DOI: 10.1139/cjfas-2019-0140
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for temperature-dependent shifts in spawning times of anadromous alewife (Alosa pseudoharengus) and blueback herring (Alosa aestivalis)

Abstract: We analyzed four decades of presence–absence data from a fishery-independent survey to characterize the long-term phenology of river herring (alewife, Alosa pseudoharengus; and blueback herring, Alosa aestivalis) spawning migrations in their southern distribution. We used logistic generalized additive models to characterize the average ingress, peak, and egress timing of spawning. In the 2010s, alewife arrived to spawning habitat 16 days earlier and egressed 27 days earlier (peak 12 days earlier) relative to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
41
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 69 publications
1
41
1
1
Order By: Relevance
“…Previous analyses of run counts in these same 12 coastal streams found that river herring run durations have not shifted substantially over recent decades (R. M. Dalton, Duke University and M. D. Staudinger, U.S. Geological Survey, unpublished data). In those analyses, run initiation was best predicted by a combination of winter variables prior to the spring run, while the median and end (Lombardo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous analyses of run counts in these same 12 coastal streams found that river herring run durations have not shifted substantially over recent decades (R. M. Dalton, Duke University and M. D. Staudinger, U.S. Geological Survey, unpublished data). In those analyses, run initiation was best predicted by a combination of winter variables prior to the spring run, while the median and end (Lombardo et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There is mounting evidence that climate change is altering the timing of migration and spawning cycles of anadromous fishes by shifting distributions, restricting suitable habitat, or shortening the window of time (i.e., phenophase) in which ideal conditions for those activities take place (Nye et al 2009; Peer and Miller 2014; Lynch et al 2015; Lombardo et al 2019; Nack et al 2019; Staudinger et al 2019). In addition, many anadromous fishes are subjected to overfishing, bycatch in marine fisheries, degradation and destruction of freshwater spawning habitat by human activities, and the obstruction of spawning migration by dams and culverts (Hall et al 2012; ASMFC 2017).…”
mentioning
confidence: 99%
See 3 more Smart Citations